2018
DOI: 10.1186/s12888-018-1643-9
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for befriending schemes: a survey of patients with severe mental illness

Abstract: BackgroundBefriending has become a widely used method for tackling social isolation in individuals with severe mental illness (SMI), and evidence exists to support its effectiveness. However, patient preferences for befriending remain unclear. We aimed to determine whether patients with SMI want a volunteer befriender and, if so, the volunteer characteristics and character of the relationship they would prefer.MethodsA survey of outpatients was conducted across London-based community mental health teams, for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The considerable variability in the uptake and use of the programme may be explained by a recent survey of out-patients with psychotic and affective disorders. 30 Patients expressed a wide range of preferences for befriending in terms of frequency and content of meetings (i.e. talking or engaging in joint activities), the duration of the programme and the background of the volunteer.…”
Section: Discussionmentioning
confidence: 99%
“…The considerable variability in the uptake and use of the programme may be explained by a recent survey of out-patients with psychotic and affective disorders. 30 Patients expressed a wide range of preferences for befriending in terms of frequency and content of meetings (i.e. talking or engaging in joint activities), the duration of the programme and the background of the volunteer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many of the challenges that were experienced could be addressed through flexibility on the part of the befriender and the programme. It has been suggested that there is not a one-size-fits-all approach to befriending individuals with mental illness, as there is a limited consensus on a range of befriending options including the variability and longevity of the programme, as well as the type of the relationship that is developed with the befriender [10,18].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…This could have caused some role ambiguity for the befriender, who may have felt pulled in different directions by the needs of the patient and the requirements of the programme, which were goal-focused in encouraging the patients to engage in more activities. Toner and colleagues [18] found that the majority of patients who were surveyed about their preferences for a befriending programme, favoured having someone to listen to and support them, rather than pushing them to do more activities. This finding might reflect some of the discomfort that befrienders felt in trying to push their match to achieve specific goals, which was sometimes met with resistance.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Furthermore, many of the challenges that were experienced could be addressed through flexibility on the part of the befriender and the befriending programme. It has been suggested that there is not a one-size-fits all approach to befriending individuals with mental illness, as there is a limited consensus on a range of befriending options including the variability and longevity of the programme, as well as the type of the relationship that is developed with the befriender (9,17).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Toner and colleagues (17) found that the majority of patients who were surveyed about their preferences for a befriending programme, favoured having someone to listen to and support them over doing more activities, which might reflect some the discomfort that befrienders felt in trying to push their match to achieve specifics goals which were sometimes met with resistance.…”
Section: Comparison With the Literaturementioning
confidence: 99%